2021
DOI: 10.1038/s41598-020-79730-z
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional causal control in the dynamics of handstand balance

Abstract: The aim of this study was to identify motor control solutions associated with the ability to maintain handstand balance. Using a novel approach, we investigated the dynamical interactions between centre of pressure (CoP) and centre of mass (CoM) motion. A gymnastics cohort was divided into a ‘less skilled’ group, who held handstands for 4–6 s, and a ‘more skilled’ group, who held handstands in excess of 10 s. CoP–CoM causality was investigated in anterior–posterior (AP) and medio-lateral (ML) directions, in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(22 reference statements)
0
3
1
Order By: Relevance
“…On the other hand, the sEMG amplitude during quiet standing showed very low values, which are in line with existing literature for resting muscle activity during balancing tasks [ 36 ]. In the frequency domain, we found no significant differences between the hand standing and the standing tasks, unlike the study by Wyatt et al 2021, which, instead, showed through a multiple regression that the frequency domain is an excellent predictor of the duration of the handstand equilibrium [ 37 ]. This is a metric that is usually used to identify patterns of fatigue.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the sEMG amplitude during quiet standing showed very low values, which are in line with existing literature for resting muscle activity during balancing tasks [ 36 ]. In the frequency domain, we found no significant differences between the hand standing and the standing tasks, unlike the study by Wyatt et al 2021, which, instead, showed through a multiple regression that the frequency domain is an excellent predictor of the duration of the handstand equilibrium [ 37 ]. This is a metric that is usually used to identify patterns of fatigue.…”
Section: Discussioncontrasting
confidence: 91%
“…This is a metric that is usually used to identify patterns of fatigue. Probably, the five-second window adopted in the present study is too short to cause fatigue [ 38 ]. Secondly, the sample was composed of expert gymnasts which are used to performing the handstand task, therefore preventing any variation in the frequency discharge of the involved muscles [ 11 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…More skilled performance is demonstrated by adaptation of reactive rather than anticipatory strategies. Mechanical advantages in mediolateral balance while standing on wider base of support are observed in more skilled athletes than in less ( Wyatt et al, 2021 ). Controlling the mediolateral CoP movement with eyes open is not essential for body stability in the frontal plane in seniors practicing gymnastics ( Puszczałowska-Lizis and Omorczyk, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, athletes exhibit postural control in sports demanding relatively swift throwing capabilities (e.g., handball and tennis), showing pronounced temporal correlations in CoP fluctuations ( Caballero et al, 2020 ; Caballero et al, 2021 ). Athletes with elevated CoP fractal dimensions along the AP axis show greater flexibility in making more sparing use of vision while finding their execution of intricate posture-motor tasks more so on proprioception ( Borzucka et al, 2020 ; Wyatt et al, 2021 ). In experimentation using galvanic vestibular stimulation (GVS) to destabilize posture, temporal correlations in CoP correlate inversely with the likelihood of post-GVS falls ( Van den Hoorn et al, 2018 ); gymnastics practice counteracts postural control disruption caused by GVS ( Hopper et al, 2014 ; Maitre and Paillard, 2016 ), although these adaptations tend to be very specific and the transfer effect is limited ( Asseman et al, 2004 ; Asseman et al, 2008 ; Paillard, 2017 ; Paillard, 2019 ).…”
Section: Introductionmentioning
confidence: 99%